Enzymatic formulation capable of degrading scrapie prion under mild digestion conditions. - Emeka A Okoroma; Diane Purchase; Hemda Garelick; Roger Morris; Michael H Neale; Otto Windl; Oduola O Abiola (PLoS ONE, 2013)
The prion agent is notoriously resistant to common proteases and conventional sterilisation procedures. The current methods known to destroy prion infectivity such as incineration, alkaline and thermal hydrolysis are harsh, destructive, environmentally polluting and potentially hazardous, thus limit their applications for decontamination of delicate medical and laboratory devices, remediation of prion contaminated environment and for processing animal by-products including specified risk materials and carcases. Therefore, an environmentally friendly, non-destructive enzymatic degradation approach is highly desirable. A feather-degrading Bacillus licheniformis N22 keratinase has been isolated which degraded scrapie prion to undetectable level of PrP(Sc) signals as determined by Western Blot analysis. Prion infectivity was verified by ex vivo cell-based assay. An enzymatic formulation combining N22 keratinase and biosurfactant derived from Pseudomonas aeruginosa degraded PrP(Sc) at 65 °C in 10 min to undetectable level -. A time-course degradation analysis carried out at 50 °C over 2 h revealed the progressive attenuation of PrP(Sc) intensity. Test of residual infectivity by standard cell culture assay confirmed that the enzymatic formulation reduced PrP(Sc) infectivity to undetectable levels as compared to cells challenged with untreated standard scrapie sheep prion (SSBP/1) (p-value = 0.008 at 95% confidence interval). This novel enzymatic formulation has significant potential application for prion decontamination in various environmentally friendly systems under mild treatment conditions.